2012
DOI: 10.1021/mp300104s
|View full text |Cite
|
Sign up to set email alerts
|

A Win–Win Solution in Oral Delivery of Lipophilic Drugs: Supersaturation via Amorphous Solid Dispersions Increases Apparent Solubility without Sacrifice of Intestinal Membrane Permeability

Abstract: Recently, we have revealed a trade-off between solubility increase and permeability decrease when solubility-enabling oral formulations are employed. We have shown this trade-off phenomenon to be ubiquitous, and to exist whenever the aqueous solubility is increased via solubilizing excipients, regardless if the mechanism involves decreased free fraction (cyclodextrins complexation, surfactant micellization) or simple cosolvent solubilization. Discovering a way to increase drug solubility without concomitant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(178 citation statements)
references
References 36 publications
5
173
0
Order By: Relevance
“…Converting a crystalline material into an amorphous form is one of the most promising ways to improve apparent solubility, since the maximum concentrations in solution achieved with the amorphous form may be significantly higher due to its higher internal energy than with its crystalline counterpart [9][10][11][12]. Furthermore, the increased apparent solubility does not decrease the drug's permeability through intestinal wall [13][14][15]. Unfortunately, the greater internal energy and molecular movement of the amorphous form may also cause the material to convert spontaneously back to its crystalline form during processing, storage or dissolution.…”
mentioning
confidence: 99%
“…Converting a crystalline material into an amorphous form is one of the most promising ways to improve apparent solubility, since the maximum concentrations in solution achieved with the amorphous form may be significantly higher due to its higher internal energy than with its crystalline counterpart [9][10][11][12]. Furthermore, the increased apparent solubility does not decrease the drug's permeability through intestinal wall [13][14][15]. Unfortunately, the greater internal energy and molecular movement of the amorphous form may also cause the material to convert spontaneously back to its crystalline form during processing, storage or dissolution.…”
mentioning
confidence: 99%
“…In the literature, it is reported that a glass solution will not influence on the permeability properties of a drug (Miller et al, 2012), and therefore it is believed that the in vivo data can be interpreted based on the dissolution data. Figure 5 shows the mean plasma concentration versus time profiles for the two ASSF formulations, and the noncompartmental pharmacokinetic parameters are provided in Table 2.…”
Section: Oral In Vivo Study In Rats Of the Glass Solution And Of Purementioning
confidence: 99%
“…The equilibrium solubility of the drug was determined at both 37°C and at room temperature (25°C), in phosphate buffer at pH 7.5, acetate buffer at pH 4.5, and maleate buffer at pH 1.0, using the shake-flask method, as previously reported (15)(16)(17). Briefly, excess amounts of pseudoephedrine were added to glass vials containing the different buffers.…”
Section: Solubility Studiesmentioning
confidence: 99%